Developing tools to enhance human memory. (Research'eu results magazine)
The EU-funded RECALL project has been exploring ways of using technology to augment human memory, for instance by feeding data from purpose-built personal memory banks onto screens and other interfaces to replay and remind people of key information from events in the recent or distant past.